Long-term dynamic simulation of environmental impacts on ecosystem-based pond aquaculture. (December 2020) - Varga, Monika; Berzi-Nagy, Laszlo; Csukas, Bela; Gyalog, Gergo
Abstract: The effect of changing environmental conditions on the operation of ecosystem-based pond aquaculture has been analyzed with long-term dynamic simulations. The applied non-conventional framework of Programmable Process Structures supports the implementation of the trans-disciplinary functionalities in a transparent structure. The developed model of medium complexity encompasses the interacting physical, chemical, biological, ecological, managerial and environmental processes in a unified, prototyped dynamic framework. This makes possible to study the effects of climate change on fishpond ecosystem and on carp growth, using 50 years long dynamic simulations. We have concluded that regardless to the limited amount of data, the approximately validated, but causally established, well-structured dynamic balance model may support the planning and operation of pond farming systems under temperate climate. Highlights: Dynamic balance modeling of ecosystem-based fishponds. Validation of the model with 10 years' data from a pond farm. Simulation based analysis of integrated biophysical and farming processes. Simulation based study of a design space to establish decision support. Long-term dynamic simulation based study of climate change effects.